Enhanced interference using microcavity structure for accurate thin film thickness measurement. Issue 12 (26th August 2015) - Feng, Yuanxiang; Chen, Shuming
Abstract : A new method based on microcavity structure is developed for accurately measuring the thickness of organic thin films. By sandwiching the thin films between a bottom reflective mirror and a top semi‐reflective mirror, the interference effect is greatly enhanced. As a result, the reflectance spectra exhibit distinctive, strong, and sharp interference peaks. The interference pattern is very sensitive to the thickness of the thin films. By fitting the interference pattern with the calculated reflectance spectra, the thickness of the thin films can be accurately determined.